The effect of Polygonum minus extract on cognitive and psychosocial parameters according to mood status among middle-aged women: a randomized, double-blind, placebo-controlled study - Shahar S (Dove Medical Press, 2015)
Suzana Shahar,1 Ainor Farahin Aziz,2 Siti Nur Arina Ismail,2 Hanis Mastura Yahya,2 Normah Che Din,3 Zahara Abdul Manaf,1 Manal M Badrasawi11Dietetics Programme, 2Nutritional Sciences Programme, 3Health Psychology Programme, School of Healthcare Sciences, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, MalaysiaBackground: Polygonum minus (PM) or locally known in Malaysia, as “kesum” is rich in micronutrients and natural antioxidants. However, its beneficial effect on outcome associates with oxidative stress including cognitive function is yet to be discovered. We assessed the efficacy of PM extract (LineMinus™) on cognitive function and psychosocial status among middle-aged women in Klang Valley of Malaysia.Methods: A randomized, double-blind, placebo-controlled trial among 35 healthy middle-aged women was performed, and subjects were randomized to receive either 250 mg PM or placebo of 100 mg maltodextrin each were taken twice daily for 6 weeks. Subjects were assessed for neuropsychological test, psychosocial status, and anthropometric at baseline, week 3, and week 6. Biomarkers were also determined at baseline and week 6.Results: The supplementation of PM showed significant intervention effect on Digit Span test (P<0.05) social functioning domain of 36-Item Short Form Health Survey (P<0.05) among subjects with mood disturbance. While, among subjects with good mood, PM supplementation improved Wechsler Abbreviated Scale of Intelligence (WASI) for IQ verbal (P=0.016) and Full Scale IQ of WASI (P=0.004). There were no adverse effects reported for the supplementation as indicated using biomarkers, including liver function and clinical symptoms.Conclusion: Supplementation of PM is safe to be consumed for 6 weeks, with potential benefits to attention, short-term memory, improved quality of life, and mood, as well as IQ.Keywords: cognitive function, P. minus, psychosocial, women, phytochemicals, quality of life